2009
DOI: 10.1017/s1368980009005837
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and vegetable consumption and its recommended intake associated with sociodemographic factors: Thailand National Health Examination Survey III

Abstract: Objective: To examine the fruit and vegetable consumption in Thailand, the percentage of Thais meeting recommended intakes and the association with sociodemographic factors. Design: Cross-sectional survey with a stratified, three-stage, cluster probability sampling design. Setting: Community-dwelling men and women participating in the Thailand National Health Examination Survey III. Subjects: A total of 39 290 individuals aged $15 years were interviewed using a questionnaire to obtain information on sociodemog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
44
9
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(85 citation statements)
references
References 19 publications
(51 reference statements)
19
44
9
1
Order By: Relevance
“…6,19,[32][33][34][35] For vegetables, Kimchi intake was higher in the low-education group, which is consistent with the results of a previous Korean study. 5 In contrast, vegetable intake without Kimchi was lower in the low-education group.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…6,19,[32][33][34][35] For vegetables, Kimchi intake was higher in the low-education group, which is consistent with the results of a previous Korean study. 5 In contrast, vegetable intake without Kimchi was lower in the low-education group.…”
Section: Discussionsupporting
confidence: 91%
“…3,4 However, most studies on SEP and FV intake have only measured intake at a single time point. [5][6][7][8][9] Although some studies have examined trends in FV intake according to SEP, these were mostly performed in the West. [10][11][12][13] Educational attainment, income and occupational social class are established indicators of SEP. 14 Of these indicators, education is the most likely to account for socioeconomic differences.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary change has been noteworthy with a nutrition transition since the early 1980s seeing sugar consumption tripling, large increases in the amounts of oils and animal proteins being consumed and decreases in fruit and vegetable consumption (Kosulwat, 2002;Satheannoppakao et al, 2009). Food types associated with these changes in the nutritive value of Thai diets are connected to rising incomes and an increasing desire for dietary convenience.…”
mentioning
confidence: 99%
“…Average daily serves of fruit and vegetables were also reported. Fruit and vegetable consumption was classified according to Thai recommended intake levels as sufficient (fruitX2 serves per day, vegetablesX3 serves per day) or insufficient (Satheannoppakao et al, 2009).…”
mentioning
confidence: 99%
“…Prior studies in Japan found that being married decreased mortality and morbidity (21,22), so married people are assumed to have a healthier diet than unmarried people. Several studies in other countries found that married individuals tend to eat healthier diets than unmarried individuals do (23)(24)(25)(26), while a few studies had inconsistent findings (27,28). Although the present study did not explore the background of the relationship, unmarried people might be likely to consume nutrient-rich food outside the home, for example.…”
Section: Discussionmentioning
confidence: 58%